Pesticide use in rice cultivation in Tarapoto, Peru - Lange, Gun (2006)
A study of the pesticide use in the rice cultivation in Tarapoto, the largest town in the department of San Martin situated in the northeast part of Peru, was performed. In Tarapoto, an irrigation canal was built in the 1980s, which gave the farmers the prerequisite to cultivate irrigated rice. The pesticides were introduced around the same time and have become a necessity to obtain a good and profitable yield.